Implementation of Building Approval Policy (PBG) in Cirebon City - Pangestu Yusuf Wijaya; Siti Khumayah (ann4publisher@gmail.com, 2026)
Background. Building Approval (PBG) is an official permit from the government that replaces the IMB, which must be obtained by building owners to build new, alter, expand, or maintain buildings, ensure compliance with technical standards and regional spatial planning for safety, comfort, health, and ease of use, and is managed through the SIBG online system. Aims. This study analyzes the implementation of the Building Approval (PBG) policy in Cirebon City using George C. Edwards III's theory. Method. This qualitative study seeks to capture the realities of the field through the voices of policymakers in DPMPTSP and DPUTR, as well as the experiences of community permit applicants. In addition, budget limitations and the number of personnel are 'sticking points' that hinder the speed of service. Results. There is a research gap indicating that PBGs offer a new approach to building licensing that focuses on meeting technical standards and professional responsibilities, in contrast to IMBs, which are administrative in nature. Conclusion. Coordination between institutions still feels complex and has not been fully integrated. Implementation: As a step forward, this research encourages strengthening human resource capacity, simplifying the digital system, and more grounded socialization to ensure that this policy is truly effective for the residents of Cirebon City.